THE EFFECT OF SALES, PRODUCTION COSTS AND TOTAL DEBT ON NET PROFIT IN REGISTERED PALM OIL PLANTATION COMPANIES ON THE INDONESIAN STOCK EXCHANGE YEAR 2017-2023 - Cut Tria Faradilla; Muttaqien; Husaini; Marzuki (Journal of Accounting Research, Utility Finance and Digital Assets, 2025)
This study aims to see the Effect of Sales, Production Costs and Total Debt on Net Profit in Palm Oil Plantation Companies Listed on the Indonesia Stock Exchange in 2017 - 2023. The data used are secondary data, the sampling technique used in this study is the purposive sampling technique and the selected samples are 22 companies. The method used to analyze the relationship between variables is panel data regression analysis. The results of the study indicate that partial sales have a positive and significant effect on profits in Palm Oil Plantation Companies on the Indonesia Stock Exchange. This shows that the more sales increase, the more the company's net profit increases. Production costs have no effect on profits in Palm Oil Plantation Companies on the Indonesia Stock Exchange. Debt Level has a negative and significant effect on profits in Palm Oil Plantation Companies on the Indonesia Stock Exchange. This shows that the more debt increases, the more net profit will decrease.